Enhanced Recovery After Caesarean Delivery Versus Standard Care Studies: A Systematic Review of Interventions and Outcomes. Issue 2 (24th June 2021) - Sultan, P.; Sharawi, N.; Blake, L.; Carvalho, B.
Abstract : ( Int J Obstet Anesthesia . 2020;43:72–86) Obstetric units worldwide are incorporating enhanced recovery after cesarean (ERAC) programs. These are multimodal care pathways aimed at improving outcomes, reducing complications and decreasing length of hospital stay. However, the ERAC interventions used, and the outcomes used to assess success of ERAC protocols vary widely. Given this, there is the need to assess the level of evidence supporting the use of ERAC. This review aimed to identify ERAC implementation studies that compared patients cared for with ERAC principles to a control group, identify specific interventions and outcome measures, and compare interventions with published guidelines, The study also reports on the impact of ERAC and the level of available evidence supporting the use of ERAC.